How does the kinase Lck phosphorylate the T cell receptor? Spatial organization as a regulatory mechanism - Rossy, Jeremie; Williamson, David J.; Gaus, Katharina (Frontiers in Immunology, 2012)
T cell signalling begins with the ligation of the T cell antigen receptor (TCR) by a cognate peptide and the phosphorylation of the receptor’s ITAM domains by the kinase Lck. However, the canonical receptor model is insufficient to explain how the constitutively active kinase Lck can discriminate between non-ligated and ligated TCRs. Here, we discuss the factors that are thought to regulate the spatial distribution of the TCR and Lck, and therefore critically influence TCR signalling initiation.